Kaifiat Corpse Training in Kaballlangan Village, Pinrang - Muliadi1, Muliadi (Jurnal Makkareso, 2023)
One of the public affairs that is always conducted is taking care of the corpse. Organizing the funeral is the main obligation for Muslims, thus, to organize the funeral requires certain knowledge, skills, and requirements so that the process can be conducted properly. In Kaballangan village, Duampanua sub-district, Pinrang district, the number of capable personnel has begun to decrease. Most of them are only religious leaders, so it is necessary to conduct regeneration to the community in this village by holding counseling about the organization of funerals. Through descriptive methods through lectures and practice. The results of the training activities for handling corpses were able to make some of the residents of Kabllangan Village volunteers who are ready at any time needed.